Transnasal hypophysectomy in conchal sella: a case report - Arora, Archana; Munjal, Manish; Singh, Damanpreet (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2016)
The trans-sphenoid access to the pituitary gland is the most common approach for pituitary adenomas. The different routes to the sella ultimately traverse the sphenoid sinus. Therefore the anatomical variations of the sphenoid sinus have major impact on the surgical access. The conchal non-pneumatized sphenoid was always considered to be a contraindication to the trans-sphenoid approach to the sella. The preset study was conducted on a 50 year old male with conchal sella with chief complains of headache and associated loss of vision in left eye is being reported. MRI brain and sella (with contrast) showed evidence of well-defined altered signal intensity in sellar and suprasellar region 12×18×15 mm. DNE showed posterior septectomy defect from previous surgery. Anterior wall of sphenoid was thick and no other landmark was identified. Keeping in midline using the sphenoid rostrum as landmark, drilling was started in 1×0.5 cm area and continued till a depth of around 1 cm till dura was visualized. Intra operative confirmation of the sphenoid and sella was done using C-ARM. It can be utilized to confirm surgical landmarks to access the sella through the sphenoid sinus accurately even in poorly pneumatized sphenoid.